Effectiveness of spiritual augmented psychotherapy on resilience and conscience on juvenile delinquents - Pragya Sahare; Anuradha Kotnala (Wolters Kluwer Medknow Publications, 2022)
Background: Resilience and conscience are the ability to endure adversity without suffering negative consequences. Psychology and spirituality can both be major assets in building resilience and conscientiousness in juvenile delinquents. Aims: The present study aims at exploring the effectiveness of psychological and spiritual techniques in mounting psychological resilience and conscience in juvenile offenders. Methods: The convenience sampling method was used to take 62 respondents for the study. They were chosen from a juvenile shelter home in Haridwar, India. The experimental group, which included 30 participants, received psychospiritual intervention as cognitive-behavioral therapy sessions and Gayatri Mantra Lekhan activity. The control group comprised another 32 volunteers who were assessed using psychometric instruments. Participants were given two psychometric scales named the Child and Youth Resilience Measure and the NEO Five-Factor Inventory for the measurement of resilience and conscientiousness, respectively. Statistical Analysis Used: The hypotheses were tested using an independent samples t-test. Results: The experimental group's mean resilience score (mean = 77.93, standard deviation [SD] = 18.28) was statistically significantly greater than the control group's mean resilience score (mean = 44.53, SD = 8.38) with t (60) = 9.35, P = 0.01 (two-tailed). The experimental group's mean conscience score (mean = 35.47, SD = 4.61) is statistically significantly higher than the control group's mean conscience score (mean = 27.34, SD = 6.38) with t (60) =5.71, P = 0.01 (two-tailed). Conclusions: The study reveals that spiritual augmented psychotherapy is significantly associated with increasing the level of resilience and conscience in the study sample.